The Odyssey of Homer: Volume 2 - Homer (London : Printed for Bernard Lintot, 1725)
This book is the 2nd of five volumes of Homer's Odyssey. It is a Greek epic poem attributed to Homer. It is one of the oldest extant works of literature still read by contemporary audiences. Divided into 24 books, it follows the Greek hero Odysseus, king of Ithaca, and his journey home after the Trojan War.
Homer's Odyssey
Translated by Alexander Pope, with the assistance of William Broome and Elijah Fenton. Volume 2 bears subtitle: Translated from the Greek. Each volume contains paper with varying watermark shields and slight foxing. Includes: "A general view of the epic poem, and of the Iliad and Odyssey. Extracted from Bossu." "Postscript by Mr. Pope"
Keywords: Rare books, Odyssey of Homer, Homer's Odyssey, The Odyssey, Homer